Ultra-flexible, stretchable, highly conductive and multi-functional textiles enabled by brush-painted PEDOT:PSS. (23rd July 2020) - Jin, In Su; Lee, Woosung; Lim, Seung Ju; Ko, Jae Hoon; Jung, Jae Woong
Abstract: Electronic textile (E-textile) with excellent electrical/mechanical properties in large area is an essential component for wearable electronics. We herein demonstrated that brush-painting is a promising printing technique of poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) on fabric substrates to prepare ultra-flexible, stretchable, and highly conductive E-textiles. The brush-painting allows uniform film surface with much lower sheet resistance which is opposite to agglomerated particulates of the film from the drop-casting. As a result, the PEDOT:PSS-based E-textiles achieve high conductivity of 6.4 S cm −1 after successive bush-painting up to 50 times with excellent mechanical properties including bending, stretching, and washing stability. The brush-painted E-textiles exhibit excellent Joule heating properties with low operative voltage and quick response time. In addition, the large-area piezoresistive sensors have been realized by the brush-painted E-textiles, suggesting its great potential of the brush-painting PEDOT:PSS toward multi-functional smart textiles or wearable electronics.